Self-veto approaches to reject atmospheric neutrinos in KM3NeT/ARCA - Heid, T.; James, Clancy; Pikounis, K. (2015)
The main objective of the future neutrino telescope KM3NeT/ARCA is the detection and measurement of high-energy extraterrestrial neutrinos. Atmospheric neutrinos, which are produced in particle showers in the Earth's upper atmosphere, represent the main background to this signal. Muon bundles which accompany down-going atmospheric neutrinos can be used to differentiate the latter from their extraterrestrial counterparts and thus to identify cosmic neutrino signals from the upper hemisphere. The program package CORSIKA has been used for simulating extensive air showers. These particle showers contain many particle types, but the only particle type except neutrinos penetrating the water layer above the detector are muons. A veto strategy against atmospheric neutrinos has been developed which uses the detector signals induced by these muons. In particular these muons modify the observed topology of neutrino-induced events, with a significant effect on different reconstruction parameters. Making use of these effects, most of the downward-going atmospheric neutrinos can be rejected. The corresponding analysis methods and results are reported.